Survey on the presence of non–dioxine‐like PCBs (NDL‐PCBs) in loggerhead turtles (Caretta caretta) stranded in south Mediterranean coasts (Sicily, Southern Italy). (26th July 2017) - Cammilleri, Gaetano; Calvaruso, Enza; Pantano, Licia; Cascio, Giovanni Lo; Randisi, Barbara; Macaluso, Andrea; Vazzana, Mirella; Caracappa, Giulia; Giangrosso, Giuseppe; Vella, Antonio; Ferrantelli, Vincenzo
Abstract: A total of 71 loggerhead turtles ( Caretta caretta ) stranded along the coasts of Sicily (Southern Italy) were examined for non–dioxine like polychlorinated biphenyl (NDL‐PCB) levels in muscle and adipose tissue by a gas chromatography‐mass spectrometry/mass spectrometry (GC‐MS/MS) method. The results revealed 6 high‐indicator congener (∑6 PCBIND ) levels in 45% of the loggerhead turtles examined, with mean values of 980.39 ± 2508.39 ng/g wet weight in adipose tissue and 102.53 ± 238.58 ng/g wet weight in muscle tissue. The hexachloro and heptachloro PCB congeners were the most abundant in both the sample types. The highest NDL‐PCB levels were reached in an adipose tissue sample of a loggerhead turtle of 80 kg stranded along the coasts of Termini Imerese (14 183.85 ng/g wet wt). No significant correlation was found between modified Fulton's K values of the loggerhead turtles and PCB contents (S = 47 151, p > 0.05). Furthermore, no significant differences were found between sexes (W = 365, p > 0.05). The PCB levels found in the present study were much higher than those found in the literature. The present study is the first report on the existence of NDL‐PCBs in loggerhead turtles stranded in Sicilian coasts confirming C. caretta as a valuable indicator of contaminant exposure in the marine environment because of their specific biological and ecological characteristics. Environ Toxicol Chem 2017;36:2997–3002. © 2017 SETAC